PERAN MARKETPLACE GO DESTINATION VILLAGE (GODEVI) DALAM MEMPROMOSIKAN DESA WISATA - Aditya, I Wayan Putra; Arini, Ni Nyoman (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 1 (2022): Jurnal IPTA (July 2022), 2022)
Government through The Ministry of Tourism and Creative Economy focuses on increasing digitization in the tourism sector. Godevi stands for Go Destination Village supports Government programs through digital applications specifically designed to tourism village empowerment. Godevi is a start up company specializing in tourism village development. Godevi is a digital platform that provides a marketplace for tourism village product and for tourist who love the authentic tourism village. Godevi also provide marketplace for local community to promote their village product. This study analyzes the roles of Godevi in promoting the Sayan Tourism Village. Sayan Village is designated as one of the tourist villages in Gianyar Regency and also is part of Godevi's partner village. Godevi's platform helps tourism villages that have difficulty in developing village potential. The existence of a tourist village platform such as Godevi in the digitalization era is expected to increase tourist visits to Sayan Village, Ubud. This study aims to identify Godevi's role in promoting Sayan Village through digital platforms. The relevant research approach used in this study is a qualitative approach. Data were collected through observation, interviews, and documentation. The result of this study refer to the presence of the Godevi marketplace is very helpful for village tourism managers in developing village product. There are four roles of Godevi in promoting the Sayan Tourism Village namely the role of digital platforms as developers, tourism village assistance, facilitator, and cooperation partner.